2006
DOI: 10.1007/s10067-006-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with anxiety and depression in fibromyalgia

Abstract: Fibromyalgia is a complex problem in which symptoms of anxiety and depression feature prominently. Low levels of vitamin D have been frequently reported in fibromyalgia, but no relationship was demonstrated with anxiety and depression. Seventy-five Caucasian patients who fulfilled the ACR criteria for fibromyalgia had serum vitamin D levels measured and completed the Fibromyalgia Impact Questionnaire (FIQ) and Hospital Anxiety and Depression Score (HADS). Deficient levels of vitamin D was found in 13.3% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 11 publications
10
137
0
6
Order By: Relevance
“…It has been reported that depression prevalence is more in obese people compared to those who are not obese up to 25 percent. On the other hand, there is a link between obesity with depression and lower levels of serum 25-hydroxyvitamin D. The prevalence of vitamin D deficiency (1), depression (2), and obesity (3) has increased rapidly in Iran during the past decade (4). Recently, the positive effect of vitamin D on the prevention and the treatment of mental health problems such as depression has been well documented (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that depression prevalence is more in obese people compared to those who are not obese up to 25 percent. On the other hand, there is a link between obesity with depression and lower levels of serum 25-hydroxyvitamin D. The prevalence of vitamin D deficiency (1), depression (2), and obesity (3) has increased rapidly in Iran during the past decade (4). Recently, the positive effect of vitamin D on the prevention and the treatment of mental health problems such as depression has been well documented (4).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a link between obesity with depression and lower levels of serum 25-hydroxyvitamin D. The prevalence of vitamin D deficiency (1), depression (2), and obesity (3) has increased rapidly in Iran during the past decade (4). Recently, the positive effect of vitamin D on the prevention and the treatment of mental health problems such as depression has been well documented (4). Divergent results have been reported concerning the relationship between Vitamin D and depression in such a manner that some cross sectional studies have found a relationship between low levels of serum 25-hydroxyvitamin D and depressive symptoms (5,6); whereas other studies of similar design have found no such relationship (7).…”
Section: Introductionmentioning
confidence: 99%
“…91 Vitamin D deficiency is also commonly observed in patients with musculoskeletal disorders like fibromyalgia and is frequently associated with depression and anxiety. 92 Severe vitamin D deficiency leads to osteomalacia and myopathy causing muscle weakness and pain often noted in type 2 diabetic patients with symptomatic relief after vitamin D replacement. 76 Therefore, early identification and correction of underlying cause such as supplementation of vitamin D and other nutritional deficiency provides a simple resolution of symptoms from musculoskeletal disorders including fibromyalgia and myofascial pain.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…In another study by Armstrong et al, FMS patients were separated into 2 groups of low level vitamin D (<25 nmol/ml) and high level vitamin D (≥25 nmol/ml). To evaluate the disease activity between the two groups, the FIQ was used and no difference was determined between the low and high vitamin D level cases in terms of FIQ [73]. In a study by Okumuş et al, 40…”
Section: Vitamin D and Quality Of Lifementioning
confidence: 99%